Risk Evaluation and Mitigation Strategies for Potential Outbreaks of Nipah Virus Infection: Evidenced by the Recent Incidences in Southeast Asian Countries - Md. Ashrafur Rahman; Yeasna Shanjana; Sydney Cronmiller; Donovan Zong; Rob Davis; Julianne Ernest; Jonah Nguyen; Amanda Rawa; Marie Roke Thomas; Md. Rabiul Islam (Health Science Reports, 2024)
ABSTRACT Background The importance of studying Nipah virus (NiV) stems from its high fatality rates and potential for causing widespread outbreaks. Recent incidences in Southeast Asian countries highlight the urgent need for effective risk evaluation and mitigation strategies. Justification Studying NiV in Southeast Asia is crucial due to the geographic and epidemiological significance that makes this region predominantly susceptible to the virus. Objectives This study aims to identify the risk factors of NiV, evaluate current mitigation strategies, and suggest improvements against this virus. Methods This review incorporates articles from the PubMed database related to available NiV treatments, vaccines, mitigation strategies, transmission data, and mortality to comprise an extensive analysis of pertinent information. Findings NiV warrants international attention, due to the high mortality rate and the rising number of human‐to‐human transmission vectors. NiV is difficult to diagnose early on in the infection due to its generic symptoms, and the two strains of NiV (B and M), pose significant challenges to healthcare institutions. Vaccines, such as the VSV‐stored, virus‐like particle‐based, and mRNA‐based NiV show promising results in both animal and human studies. Synthetic medicines, like Ribavirin, and favipiravir showed promising results in NiV‐infected patients. Therapeutic infectious particles increased survival from 10% to roughly 70%–80% in animals. Phytochemicals, like serpentine and neoandrographolide are alternatives to NiV‐G ligands. Griffithsin, an algae derivative has also shown efficacy in treating NiV infections. Artificial intelligence determines the NiV infection with an accuracy of 88.3%. Conclusions The strategies to control NiV must be one of a One Health approach, incorporating environmental and social factors. Extensive research on vaccines that showed promising results in animals needs to be tested for humans on a large scale. The major mitigation strategy available is the public awareness during the outbreak about NiV transmission vectors, quarantine protocol, and food hygiene.